M22 Nebulised antibiotic challenges: can the process be made more efficient for patient and clinician?. (12th November 2019) - Forrester, J; Paramasivan, C; Pickover, C; Sander, C
Abstract : Aim: We hypothesis that current recommended nebulised antibiotic challenge procedures, particularly the 30 minute post nebuliser spirometry, may not alter clinical decisions whilst incurring unnecessary clinician time and service provision Background: Nebulised antibiotics are an alternative therapy option in patients with lung disease that often colonise specific bacteria in sputum. BTS guidance for Bronchiectasis (2018) provide a standard framework for the procedure of assessing patients' suitability for these medications. At present the procedure recommends spirometry; pre nebuliser, immediately post, 15 minutes post and 30 minutes post. If any FEV1 does not drop >15% over the test time then they are suitable. Conversely ERS recommend immediate and post 30 minute spirometry with a 10% allowance. These recommendations, however, come with little evidence backing particularly regarding timings of spirometry post nebulisation Method: We completed a retrospective review of patient data going back to 2015. For each challenge the spirometry was collected pre, immediately and 30 minutes post. Results: 70 patients underwent testing from September 2015. Based on BTS guidance 2 patients were deemed unsuitable from immediate post spirometry (2.86%). Using the ERS guidance 6 patients were deemed unsuitable immediately post (8.57%). 1 patient assessed had a drop at 30 minutes but initial spirometry was stable. No patient had changes that altered clinical decisions Discussion: This small data set presents evidence that spirometry beyond the immediate post may not provide information that alters clinical decision. Patients were deemed unsuitable based on immediate post nebuliser and not based on subsequent spirometry. It may be suitable, therefore, to propose alternative assessment methods whereby immediate spirometry is completed and if stable the patients are suitable. In the event of symptoms being reported or drop in spirometry then further spirometry at 30 minutes should be completed. This could have profound implications on appointments, clinician time and costing.